Perlindungan Hukum Terhadap Pegawai Notaris Sebagai Saksi Instrumenter Dalam Akta Notaris - Rahmadany, Deya Nathasya; Subekti, Sri (UNES Law Review, 2024)
Notary employees have quite a big role and position in assisting the performance of notaries in deed making services. In addition to assisting the Notary's performance in carrying out his or her position optimally, a Notary employee must also be able to act as an instrumental witness in the preparation and inauguration of a Notary's deed as long as it meets the requirements as stated in Article 40 paragraph (2) of the Notary's Position Law, namely that the witness must be at least 18 years old. years old or married, competent in legal actions, understands the language used in the deed, can sign and initial, and does not have a marital relationship with the Notary or the parties. As a Notary employee who acts as an instrumental witness in the inauguration of a deed which of course has entered into legal traffic and gives rise to legal consequences, so that if a Notarial deed later arises in a problem or case then the Notary employee will be involved in the problem or case. Like witnesses in other cases, Notary employees as witnesses in Notarial deeds should also receive legal protection and their safety must be guaranteed in the event of a case or lawsuit in court regarding a deed in which the Notarial employee is a witness. Although the actions of Notary employees as instrumental witnesses in the officiating of notarial deeds are included in the field of notarial matters, the Law on the Position of Notaries does not provide legal protection for witnesses in the officiating of deeds, especially for Notary employees. This is because in the UUJN only Notaries receive legal protection, so legal protection for Notary employees as instrumental witnesses in the inauguration of Notarial deeds is not found in the Law. In the absence of regulations in the Notary Position Law regarding protection for Notary employees who are instrumental witnesses in the inauguration of deeds, legal protection for Notary employees who are witnesses can only be found in provisions outside the Notary position regulations, namely Law Number 13 of the Year 2006 concerning Witness and Victim Protection. Even though the Law does not specifically regulate witnesses in the formalization of Notarial deeds, the provisions in the Law can be applied to the position of Notary employees as instrumental witnesses in the formalization of deeds, namely in the event that the witness is summoned in a case process.